FORMULATION AND IN VITRO EVALUATION OF BROMOCRIPTINE MESYLATE AS FAST DISSOLVING ORAL FILM - Tamer, Manar Adnan; Hammid, Shaimaa Nazar Abd-al; Ahmed, Balqis (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of this study was to formulate and in vitro evaluate fast dissolving oral film of practically insoluble bromocriptine mesylate to enhance its solubility and to improve its oral bioavailability by avoiding first pass effect as well as to produce an immediate release action of the drug from the film for an efficient management of diabetes mellitus type II in addition to an improvement of the patient compliance to this patient-friendly dosage form. Methods: The films were prepared by the solvent casting method using hydroxypropyl methylcellulose of grades (E3, E5, E15), polyvinyl alcohol (PVA), pectin and gelatin as film-forming polymers in addition to polyethene glycol 400 (PEG400), propylene glycol (PG) and glycerin were used as a plasticizer. Poloxamer 407 was used as a surfactant, sodium saccharin as a sweetening agent, citric acid as a saliva stimulating agent, vanilla as a flavouring agent and crospovidone as a super disintegrant. The prepared films then tested for physical characterization, thickness, weight uniformity, mechanical characteristics (folding endurance, tensile strength, percent elongation and Young's modulus), surface pH, in vitro disintegration time, drug content and an in vitro drug release. Results: Films were found to be satisfactory when evaluated for physical characterization, thickness, weight uniformity, mechanical tests, in vitro disintegration time, folding endurance, drug content and an in vitro drug release. The surface pH of all the films was found to be neutral or minor change. Films in vitro drug release studies were also done using USP dissolution apparatus type II (paddle type). The in vitro drug release profile in the optimized formulation F14 was gave 86.8 % of drug released at 2 min. The optimized formulation F14 was also showed satisfactory pH (6.2±0.2), drug content (99.2±0.5%), the disintegration time of 9.2±0.1 seconds and the time needed for 80% of medication to be released (T80 %) was 1.35 minute. Conclusion: The bromocriptine mesylate fast dissolving oral film was formulated. The given film disintegrates within nine seconds which release the drug rapidly and gives an action.